Adsorpsi Logam Timbal (Pb) dari Larutannya dengan Menggunakan Adsorben dari Tongkol Jagung - Ningsih, Dwi Arista; Said, Irwan; Ningsih, Purnama (Jurnal Akademika Kimia, 2016)
Heavy metals will cause environmental problems. One of the efforts that can minimize level of heavy metal from their solutions is to reduce heavy metals content, so that safely discarded at sea/river. One such way to reduce level of heavy metals is by adsorption. Some agricultural waste are potential as an adsorbent, namely a corncob. Therefore, the aim of this study is to determine the optimum weight of adsorben from corncob to absorb Pb(II) from its solution. In this study, the corncob was used as an adsorbent to adsorb Pb(II) by using three methods, namely powder, charcoal and activated charcoal with a solution of HCl. The parameters tested were amount of adsorbent or weight of the powder, charcoal and activated charcoal by the weight variation of 20, 40, 60, 80 and 120 mg to determine the optimum conditions in adsorbing Pb(II). The optimum conditions are obtained for the powder was 80 mg with the absorption of 96.92%, the charcoal is 80 mg with absorption of 97.29%, and the activated charcoal was 40 mg with the absorption of 94.70%.